Kissometer / Suhaida Ab Wahab and Azizah Md Salleh - Ab Wahab, Suhaida; Md Salleh, Azizah (2003)
The project, “Kissometer”, is very much an arbitrary title; as you will see, with simple label changes it could be called almost any other kind of …..-ometer. Kissometer, in essence, the principle goes like this: Place one’s finger, or perhaps other bodily appendage, upon some touch pad contacts. Wait for auditory sense to be sufficiently stimulated: lift your clammy finger - and take delight in the visual wonder that is ….. , well, the means by which the Kissometer judges your “Kissability”, aggressiveness. As we can see, we can always change this usage. As we know, it can be any meter. So we suggest that it is use in the classroom by the teacher as an equipment to select question while their doing quizzes. The teacher can label the meter such as, simple, quite simple, tough, quite tough and very tough. It will be interesting while it is affordable. The jumping light emitting diode (L.E.D) dot display will gradually slow down until it settles and stops so as to light only one L E D. the label adjacent to the lit L.E.D now indicates your rating. The more observant individuals amongst us will realize that this “decision” is an almost perfectly random indication But just remember, that skin resistance falls as vigorous hormone activity cause small yet detectable changes in body perspiration. It’s the truth, honestly.